Internalisasi Nilai Budaya Kerja Kementerian Agama dalam Pembentukan Disiplin Kerja PPPK di UIN Sultan Aji Muhammad Idris Samarinda - Achmad Farihin; Eka Mahmud; Bahrani Bahrani (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
The internalization of organizational work values is essential for developing employee discipline, yet little is known about how the five core work values of the Indonesian Ministry of Religious Affairs are embedded among Government Employees with Work Agreements (PPPK) in Islamic higher education institutions. This study examines the internalization process, the factors that support and hinder it, and its implications for work discipline among educational support staff at Sultan Aji Muhammad Idris State Islamic University Samarinda. A qualitative case study design was employed. Data were collected through observations, in-depth interviews, and document analysis involving fifteen informants, including university leaders, administrative managers, and PPPK educational staff. Data credibility was ensured through source and method triangulation, member checking, and an audit trail, while analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings show that the internalization of the Ministry's five work values—integrity, professionalism, innovation, responsibility, and exemplary conduct—is fostered through continuous socialization, employee development, leadership role modeling, supervision, performance evaluation, and workplace habituation. Its effectiveness is strengthened by committed leadership, effective communication, and consistent performance monitoring, but constrained by differences in employees' adaptability, regulatory understanding, and communication practices. The study further demonstrates that work discipline develops not merely through compliance with organizational rules but through the sustained internalization of shared values. These findings culminate in a conceptual model that explains how value internalization shapes PPPK work discipline, offering both theoretical insights into organizational culture and practical guidance for human resource management within the Ministry of Religious Affairs.